Migrating For Freedom, Migrating into Slavery: 21st Century Ironies - Odimegwu, Ike; Ogugua, Christopher (Social Science Research, 2024)
Migration has been part of the natural dispositions and existential manifestation of humankind. And it has been part of the history as well as a fundamental tool in the making of the histories of nations and peoples. However, in recent times, there has been an increase in global movement of people, especially from the less industrialized economies of the Global South to the more industrialized economies of the Global North. This upsurge has made migration a central global issue for policymakers and scholars of diverse fields in the 21st century. The paper examines the various causes of the migration surge in the 21st century and the different restrictive measures employed especially by the economically prosperous countries of the Global North to cut the flow of immigration into their countries. The paper discusses how so many people from the less economically prosperous countries, who leave their countries of origin in search of freedom and the opportunities thereof, end up either in physical slave camps in countries like Libya and Mexico, or in virtual slave camps in dehumanizing conditions in Europe, North America and other parts of the world.